Parental and Sibling Confinement: Exploring Their Role in Youth Mental Health - Fernandes, April D. (American journal of criminal justice, 2025)
Existing research shows detrimental mental health effects of incarceration for youth, suggesting that the lived reality of confinement results in higher levels of depression and anxiety (Fagan & Kupchik, 2011; Forrest et al., 2000). A growing body of empirical work has explored the vicarious health effects of parental and sibling incarceration (Lee & Wildeman, 2021; Haskins, 2015). However, such inquiries have generally not included system-linked youth nor other modes of confinement. Using data from the Northwest Juvenile Project (NWP), this exploratory study explores the ways that early parental and sibling confinement, including incarceration and mental health hospitalization, affects the mental health outcomes of more than 1,800 system-involved youth in Cook County, Illinois. Our findings dovetail with existing empirical results, which suggest that the impacts of incarceration and mental health hospitalization are complex, finding other contextual factors can be more influential on levels of depression and anxiety for youth. Such an investigation adds to the emerging scholarship on the complex ways early familial incarceration can impact youth as they navigate their own contact with the criminal legal system and incarceration.